Drosophila Model for the Analysis of Genesis of LIM-kinase 1-Dependent Williams-Beuren Syndrome Cognitive Phenotypes: INDELs, Transposable Elements of the Tc1/Mariner Superfamily and MicroRNAs - Savvateeva-Popova, Elena V.; Zhuravlev, Aleksandr V.; Brázda, Václav; Zakharov, Gennady A.; Kaminskaya, Alena N.; Medvedeva, Anna V.; Nikitina, Ekaterina A.; Tokmatcheva, Elena V.; Dolgaya, Julia F.; Kulikova, Dina A.; Zatsepina, Olga G.; Funikov, Sergei Y.; et al. (Frontiers in Genetics, 2017)
Genomic disorders, the syndromes with multiple manifestations, may occur sporadically due to unequal recombination in chromosomal regions with specific architecture. Therefore, each patient may carry an individual structural variant of DNA sequence (SV) with small insertions and deletions (INDELs) sometimes less than 10 bp. The transposable elements of the Tc1/mariner superfamily are often associated with hotspots for homologous recombination involved in human genetic disorders, such as Williams Beuren Syndromes (WBS) with LIM-kinase 1-dependent cognitive defects. The Drosophila melanogaster mutant agnts3 has unusual architecture of the agnostic locus harboring LIMK1: it is a hotspot of chromosome breaks, ectopic contacts, underreplication, and recombination. Here, we present the analysis of LIMK1-containing locus sequencing data in agnts3 and three D. melanogaster wild-type strains – Canton-S, Berlin and Oregon-R. We found multiple strain-specific SVs, namely, single base changes and small INDEls. The specific feature of agnts3 is 28 bp A/T-rich insertion in intron 1 of LIMK1 and the insertion of mobile S-element from Tc1/mariner superfamily residing ~ 460 bp downstream LIMK1 3’UTR. Neither of SVs leads to amino acid substitutions in agnts3 LIMK1. However, they apparently affect the nucleosome distribution, non-canonical DNA structure formation and transcriptional factors binding. Interestingly, the overall expression of miRNAs including the biomarkers for human neurological diseases, is drastically reduced in agnts3 relative to the wild-type strains. Thus, LIMK1 DNA structure per se, as well as the pronounced changes in total miRNAs profile, probably lead to LIMK1 dysregulation and complex behavioral dysfunctions observed in agnts3 making this mutant a simple plausible Drosophila model for WBS.